LABORATORY PLANT FOR CRUSHING SOLID MATERIALS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article discusses the design, operation, and performance of a laboratory-scale plant for crushing solid materials. The study aims to analyze the efficiency, energy consumption, and material behavior during the crushing process. The experimental setup and methodologies used in this study are detailed, followed by a comprehensive analysis of the results. Conclusions drawn from the study offer insights into optimizing crushing processes in laboratory settings and provide suggestions for future research.